Analysis of Supply Chain Performance of Mackerel Fish (Scomberomorus commerson) in Tanjung Medang Village, Rupat Utara Sub-District, Bengkalis Regency, Riau Province - Linda Safitri; Eni Yulinda; Trisla Warningsih (Jurnal Perikanan dan Kelautan, 2024)
The fisheries potential in Tanjung Medang Village is highly promising for development due to its predominantly coastal location. This research aims to identify the mackerel supply chain pattern in Tanjung Medang Village using the Food Supply Chain Network (FSCN) approach. The method used is a survey method. Data analysis uses supply chain pattern analysis with the FSCN approach. The research results show that the mackerel supply chain pattern in Tanjung Medang Village has a supply chain structure consisting of primary and secondary members. Supply chain targets include the export market (Malaysia) and the local market (Tanjung Medang). The application of supply chain management includes bound and unbound partner relationships between supply chain actors, contractual agreements that occur informally, and transactions between supply chain actors using credit and prepayment systems. Supply chain business processes include collaborative planning that appears in each supply chain actor; the risks faced by each supply chain actor are different. The resources owned by the supply chain are by needs (physical resources, capital, technology, and human resources).